2023
DOI: 10.1111/icad.12705
|View full text |Cite
|
Sign up to set email alerts
|

Butterfly community composition within a tropical urban landscape is influenced by habitat type and temperature

A. Ombugadu,
Z. A. Hassan,
J. I. Ibrahim
et al.

Abstract: The specific factors that influence spatial community or population dynamics are often elusive, and even less known is the impact of tropical urban landscapes on diverse species community assemblages. To address this knowledge gap, we used a survey data set with 510 fruit‐feeding butterflies comprising 20 species across two heterogeneous habitats within a city in Nigeria. Next, we constructed generalised linear mixed models to understand the differential responses of the butterfly community to changes in envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 84 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Many works indicate a homogenisation and decrease in functional type, species diversity and/or insect abundance as urban density increases (in this SI see: Barao et al, 2024;Casanelles-Abella et al, 2024;Federico et al, 2024;Rivest & Kharouba, 2024;Sanetra et al, 2024;Svenningsen et al, 2024). This picture is, however, nuanced (e.g., Ancillotto & Rocco, 2024;Federico et al, 2024;Ombugadu et al, 2024) and although urban areas can detrimentally impact some insect taxa through the predominance of artificial environments, constrained habitats and disturbances, other taxa can adapt and thrive in the mosaic of semi-natural and novel environments, management variation and abundant resources (Curry et al, 2024;Hill et al, 2024;Nunes et al, 2024;Plummer et al, 2024;Xu et al, 2024).…”
Section: In Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…Many works indicate a homogenisation and decrease in functional type, species diversity and/or insect abundance as urban density increases (in this SI see: Barao et al, 2024;Casanelles-Abella et al, 2024;Federico et al, 2024;Rivest & Kharouba, 2024;Sanetra et al, 2024;Svenningsen et al, 2024). This picture is, however, nuanced (e.g., Ancillotto & Rocco, 2024;Federico et al, 2024;Ombugadu et al, 2024) and although urban areas can detrimentally impact some insect taxa through the predominance of artificial environments, constrained habitats and disturbances, other taxa can adapt and thrive in the mosaic of semi-natural and novel environments, management variation and abundant resources (Curry et al, 2024;Hill et al, 2024;Nunes et al, 2024;Plummer et al, 2024;Xu et al, 2024).…”
Section: In Summarymentioning
confidence: 99%
“…Appropriate climate and temperature are crucial for all ectothermic organisms; accordingly, strong associations are reported between urban temperatures, the abundance and species richness of many taxa (Hansen et al, 2005) and the variability of phenotypes identified among populations dispersed along a gradient of urban intensity (Merckx, Kaiser, & Van Dyck, 2018;Merckx, Souffreau, et al, 2018;Ombugadu et al, 2024). These patterns are the outcomes of physiological (Hamblin et al, 2017) and metabolic (Chown & Duffy, 2015) opportunities and constraints, which shape individual life-history trait expression, phenological timing and may affect immunity (Merckx, Kaiser, & Van Dyck, 2018;Merckx, Souffreau, et al, 2018).…”
Section: Anthropogenic Pollution: Heat Noise Light and Other Contamin...mentioning
confidence: 99%
See 1 more Smart Citation